DETERMINATION OF SOME MINERAL ELEMENTS LEVEL IN VEGETABLES SOLD IN YANKABA MARKET KANO STATE, NIGERIA - Umar, Hauwa Mohammed; Mohammed, Musa Ibrahim (FUDMA JOURNAL OF SCIENCES, 2023)
This study was conducted to analyze the levels of some mineral element contents of broccoli, cauliflower, curly kale, red cabbage, and lentils sold in Yankaba Market of Kano State, Nigeria. Samples of these vegetables were obtained from the market and analyzed for some mineral elements (calcium, Cobalt, Copper, iron, potassium, magnesium, manganese, sodium, and zinc) contents using standard methods. The mineral elements analysis showed that the samples had calcium ranging from 43.09 to 76.67 mg/kg, cobalt 0.04 to 2.33 mg/kg, Copper 0.89 to 7.20 mg/kg, iron 0.71 to 9.88 mg/kg, Potassium 12.83 to 69.09 mg/kg, magnesium 15.63 to 86.63 mg/kg, Manganese 0.51 to 1.77 mg/kg, Sodium 8.65 to 37.36 mg/kg, and Zinc 0.7-11.88 mg/kg. atomic absorption spectroscopy (AAS) method was used to determine the level of these elements. The results for the analysis of variance (ANOVA) indicated that (P>0.05) in all samples, this shows that there was no significant difference among the samples analyzed.  The study revealed that the vegetables from the Yankaba market contain some appreciable amount of essential nutrients and mineral elements needed to maintain good nutritional status that will benefit consumers.
Keywords: Yankaba market; broccoli; cauliflower; curly AAS